Traces of the Sámi case system in the indrefinnmarksmål dialect - Bratina, Tomáš (Studia Scandinavica, 2024)
The article deals with the Norwegian dialect of the interior of Finnmark county. This is an area thathas historically been closely linked to the Finno-Ugric population. The coexistence of Norwegianas a representative of the Indo-European languages and Sámi as a representative of the Uraliclanguages may have resulted in several specific features. The aim of this article is to identify thosefeatures related to the Sámi case system: occurrence of atypical prepositions and an unusuallocal perspective. In my analysis, I rely on data from the Nordic Dialect Corpus (Nordiskdialektkorpus) – an electronic database that contains records of authentic dialect conversationsin various regions of Norway. The interior of the county of Finnmark is represented by threeplaces: Kautokeino, Tana and Lakselv.